An effective performance appraisal system as perceived by officers of Bank Bumiputra Malaysia Berhad - Ibrahim, Partini (1998)
The purpose of this study is to examine shortcomings and characteristics of an effective performance system development as perceived by the officers of BBMB. A total of 123 officers consisting of managers, deputy managers and accountants from the region of Wilayah Persekutuan, Kuala Lumpur have been selected using stratified random sampling technique. Data collection was approached in two modes i.e. by using a personal face-to-face interview and structured self-administered questionaires. Data were analysed with the use of Statistical Package for Social Science (SPSS). Frequencies and percentages were employed in descriptive analyses while the relationship between the socio-employment variables and Performance Appraisal System (PAS) variables was analysed by using Pearson Product - Moment Correlation. The results of the study revealed that there are a number of major shortcomings of the current PAS which need to be addressed by the Bank in developing an effective PAS. It is further concluded that an effective PAS should comprised of performance planning process, performance coaching process, performance review process and performance appraisal process. There is no significance differences on responses of male and female respondents towards the planning process, coaching process, review process and performance appraisal process. However, there were significant differences between managers' and executives' responses towards coaching and reviewing processes. On the other hand length of service is negatively related to planning process and therefore long service officers do not see planning process as a characteristic of an effective PAS. The study as a whole supported the existing concepts, appraisal approaches, models and research on PAS. It is also contributed significantly to the understanding of the characteristics of an effective PAS. As for the Malaysian environment is concerned, the study can be described as explanatory or as a bench-mark attempt to empirically look at the characteristics of an effective PAS. The study has therefore recommended further research undertaking on replication of the current study to cover other region in order to provide more concrete findings and conclusions in relation to characteristics of an effective PAS, to carry out study on external factors that affect the effectiveness of PAS and finally to explore the development of performance based rewards system